2023
DOI: 10.3390/polym15183822
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Calcium–Phosphate Materials for Bone Grafting

Oleg Mishchenko,
Anna Yanovska,
Oleksii Kosinov
et al.

Abstract: Synthetic bone grafting materials play a significant role in various medical applications involving bone regeneration and repair. Their ability to mimic the properties of natural bone and promote the healing process has contributed to their growing relevance. While calcium–phosphates and their composites with various polymers and biopolymers are widely used in clinical and experimental research, the diverse range of available polymer-based materials poses challenges in selecting the most suitable grafts for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 464 publications
1
5
0
Order By: Relevance
“…In our opinion, the data obtained in this study confirm that, as reported in the literature, the β-TCP matrices produced using our top-down DLP present promising properties for bone tissue engineering [33]. In fact, we demonstrated that the purity of β-TCP powder and the physico-chemical properties and biocompatibility of matrices are not altered by our printing process [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our opinion, the data obtained in this study confirm that, as reported in the literature, the β-TCP matrices produced using our top-down DLP present promising properties for bone tissue engineering [33]. In fact, we demonstrated that the purity of β-TCP powder and the physico-chemical properties and biocompatibility of matrices are not altered by our printing process [34].…”
Section: Discussionsupporting
confidence: 88%
“…Even though our study focused on β-TCP, other calcium phosphate synthetic apatites, like HA and biphasic calcium phosphate (BCP), a mixture of hydroxyapatite and β-TCP, can also be considered because of their specific biological and mechanical properties [13,33]. However, depending on the synthetic calcium apatite composition, specific formulations of polymer binders are necessary if we want to obtain high-density matrices with optimised properties [44,45].…”
Section: Purity and Biocompatibility Of 3d-printed Matricesmentioning
confidence: 99%
“…This study investigated a viable alternative to be used in dentistry and regenerative medicine for the treatment of mandibular lesions, given that this clinical condition has a direct impact on patients’ quality of life and on the resources allocated to healthcare for these purposes [ 56 , 57 ]. Therefore, the ability of plant extracts (pomegranate and jatoba) to stimulate osteogenesis in polymeric scaffolds during the bone repair process of defects created in the mandibular ramus of rats was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to HA, β-TCP has enhanced biodegradability and resorption rates, which may increase the biocompatibility of implants. The β-TCP has a lower resorption rate relative to α-TCP, and the nanoporous structure of β-TCP provides improved biomineralization, cell adhesion, and osteoblast proliferation [19].…”
Section: Discussionmentioning
confidence: 99%